Machine Learning as a method of adapting offers to the clients - Bielecki, Jacek; Ceglarski, Oskar; Skublewska-Paszkowska, Maria (Journal of Computer Sciences Institute, 2019)
Recommendation systems are class of information filter applications whose main goal is to provide personalized recommendations. The main goal of the research was to compare two ways of creating personalized recommendations. The recommendation system was built on the basis of a content-based cognitive filtering method and on the basis of a collaborative filtering method based on user ratings. The conclusions of the research show the advantages and disadvantages of both methods.